Factors That Related with Incomplete Children Immunization in Kuala Tungkal II Health Center - Yundri Yundri; Mexitalia Setiawati; Suhartono Suhartono; Henry Setyawan; Kamilah Budhi (Universitas Airlangga, 2017)
Complete basic immunization coverage in West Tanjung Jabung Barat District has not reached the Millennium Development Goals standard (> 93%). Data from the Health Office shows that the achievement of complete basic immunization in West Tanjung Jabung District was 89% and the working area of the Public Health Center (PHC) of Kuala Tungkal II in West Tanjung Jabung District was 78%. The main causes of the low achievement of basic immunization are the characteristics and behavior of the mother. This study aims to analyze the factors associated with the incompleteness of basic immunization status. This research is a mixed-methods research which includes cross-sectional and qualitative studies using in-depth interviews. The study was conducted in the working area of PHC of Kuala Tungkal II, West Tanjung Jabung District. The population in this study is all mothers who have children aged 12 to 24 months. Sampling is done through a random sampling probability technique. The results showed that there was a significant relationship between maternal knowledge (p=0,000; OR=45.25; 95%CI=13.23-154.72), the attitude of mothers in need of immunization (p=0,000; OR=94.55; 95%CI=22.13-403.87), maternal motivation in taking immunization time (p=0,000; OR=37.00; 95%CI=11.40-119.99) is related to the child's basic immunization status. The conclusion of the research is that the three variables are related to the incompleteness of immunization. Research suggestions are addressed to the health department to increase the knowledge of health workers in training related to basic immunization, so as to provide counseling to the public about the importance of basic immunization in children.